PENGARUH KEPUTUSAN MAHKAMAH INTERNASIONAL DALAM SENGKETA PULAU SIPADAN DAN LIGITAN TERHADAP PENETAPAN GARIS PANGKAL KEPULAUAN INDONESIA - Popi Tuhulele (Faculty of Law, Universitas Pattimura, 2011)
International Court of Justice Decision established Sipadan and Ligitan islands as a part of Malaysia’s souverign. This decision gives significant influenced for Indonesia and Malaysia, pariculary for Indonesia’s souvereignity. It’s important for Indonesia to made change of the position of archipelagic baselines were previously located for these two island. The changing of basilines position has influenced for Indonesia’s rules of territorial sea boundary, contiguous zone, exclusive economic zone, continental shelf, archipelagic waters and internal waters. Based on UNCLOS 1982, the exact position of each boundaries is still need to resolved further by both countries, because its should not be set unilaterally. Billateral cooperation between these two countries give oppurtunity to solved this problem equally.